Prolonging hypothermic ischaemic cardiac and vascular storage by inhibiting the activation of the nuclear enzyme poly(adenosine diphosphate-ribose) polymerase - Korkmaz-İçöz, Sevil; Loganathan, Sivakkanan; Li, Shiliang; Ruppert, Mihály; Brlecic, Paige; Karck, Matthias; Szabó, Gábor (European journal of cardio-thoracic surgery, 2017)
Abstract. OBJECTIVES: Heart transplantation is the standard treatment in end-stage heart failure and at shortage of cardiac allografts is its major limiting fa